Budaya Patriarki dalam Rumah Tangga: Telaah Hermeneutik Atas Penafsiran Qs. An-Nisa: 34 dalam Perspektif Kesetaraan Gender - Nurul Mausufi; Chufriani Tanjung; Rizki Rahmadiansyah Kurniawan; Achyar Zein; Rahayu Fuji Astuti (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Patriarchal culture has deeply rooted itself in the majority of countries around the world. The perceived superiority of men over women extends into various sectors of life, resulting in the marginalization of the significant roles women play. Unfortunately, this patriarchal culture is often justified by interpretations of Qur'anic verses, including Q.S. An-Nisa: 34. This research employs a conceptual thematic method. The type of research used is library research, which relies on literature sources. The approach adopted is the double movement hermeneutics of Fazlur Rahman and hermeneutics of Rasyid Ridha. This approach is used to uncover the historical context of the verse, in order to extract its moral ideas for application in the present day. The findings of this research show that, from a historical perspective, Q.S. An-Nisa: 34 was revealed as a response to the deeply entrenched patriarchal culture among the Arab people. This verse contains three core moral ideas: it implies the obligation of a husband as the head of the household to provide for and protect his wife; it indicates the responsibility of a good wife to guard herself; and it outlines the method for addressing a wife’s disobedient behavior (nusyūz). These three moral ideas suggest that husbands and wives are, in essence, family partners with equal rights, responsibilities, and status.